PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI ASN DINAS PERPUSTAKAAN DAN KERASIPAN PROVINSI BENGKULU - Meiffa Herfianti; Mimi Kurnia Nengsih (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
The purpose of this study was to determine the effect of leadership style and work environment on the performance of employees at the Bengkulu Province Library and Archives Service. This research is a quantitative study with a total sample of 79 employees of the Library and Archives Office of Bengkulu Province. Data collection using a questionnaire and multiple linear regression analysis method, determination test and hypothesis testing. The results of the regression analysis showed Y = 8.641 + 0.312X1 + 0.492 X2. This means that there is a significant positive influence between X1 (Leadership Style) and X2 (Work Environment) on employee performance (Y).